Relativistic recoil, electron-correlation, and QED effects on the $2{p}_{j}$-$2s$ transition energies in Li-like ions - Kozhedub, Yury; Volotka, A. V.; Artemyev, Anton; Glazov, D. A.; Plunien, G.; Shabaev, V. M.; Tupitsyn, I. I.; Stöhlker, Thomas (Physical review. A, Atomic, molecular, and optical physics, 2010)
The relativistic nuclear recoil, higher-order interelectronic-interaction, and screened QED corrections to the transition energies in Li-like ions are evaluated. The calculation of the relativistic recoil effect is performed to all orders in 1/Z. The interelectronic-interaction correction to the transition energies beyond the two-photon-exchange level is evaluated to all orders in 1/Z within the Breit approximation. The evaluation is carried out employing the large-scale configuration-interaction Dirac-Fock-Sturm method. The rigorous calculation of the complete gauge invariant sets of the screened self-energy and vacuum-polarization diagrams is performed utilizing a local screening potential as the zeroth-order approximation. The theoretical predictions for the 2pj-2s transition energies are compiled and compared with available experimental data in the range of the nuclear charge number Z=10-60.
Gesehen am 23.03.2023